“The Opposite of History is Forgetfulness”:: Myth, History, and the New Dominion in Jane Urquhart’s Away - Wyile, Herb (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 1999)
Jane Urquhart's Away provides a moving illustration of Eli Wiesel's adage that "the opposite of history is forgetfulness." As a historical novel, Away lacks the discursive heterogeneity and interrogativeness typical of the historiographical metafiction so prevalent in recent English-Canadian novels. Instead, its blending of historical realism and the marvelous provides a more seamless and less openly dialogic postcolonial historicizing of myth, raising questions about migration, identity, power, and the force of nationalism. Away also provides an allegorical engagement with the degradation of the environment in contemporary capitalist society. The generic features of magic realism are aptly suited to dramatizing the complex relationship between myth, history, politics, and cultural identification, as the rich blend of historical realism, fantasy and folklore in Away illustrates.